Anodal Transcranial Direct Current Stimulation Enhances Retention of Visuomotor Stepping Skills in Healthy Adults - Tseng, Shih-Chiao; Chang, Shuo-Hsiu; Hoerth, Kristine M.; Nguyen, Anh-Tu A.; Perales, Daniel (Frontiers in Human Neuroscience, 2020)
Transcranial direct current stimulation (tDCS) paired with exercise training can enhance learning and retention of hand tasks; however, there have been few investigations of the effects of tDCS on leg skill improvements. The purpose of this study was to investigate whether tDCS paired with visuomotor step training can promote skill learning and retention. We hypothesized that pairing step training with anodal tDCS would improve skill learning and retention, evidenced by decreased step reaction times, both immediately (online skill gains) and 30 min after training (offline skill gains). Twenty healthy adults were randomly assigned to one of two groups, in which 20-min anodal or sham tDCS was applied to the lower limb motor cortex and paired with visuomotor step training. Step reaction times (RTs) were determined across three time points: (1) before brain stimulation (baseline), (2) immediately after brain stimulation(P0), and (3) 30 min after brain stimulation (P3). A continuous decline in RT was observed in the anodal tDCS group at both P0 and P3, with a significant decrease in RT at P3; whereas there were no improvements in RT at P0 and P3 in the sham group. These findings do not support our hypothesis that anodal tDCS enhances online learning, as RT was not decreased significantly immediately after stimulation. Nevertheless, the results indicate that anodal tDCS enhances offline learning, as RT was significantly decreased 30 min after stimulation, likely because of tDCS-induced neural modulation of cortical and subcortical excitability, synaptic efficacy, and spinal neuronal activity.